Beyond restenosis: Patients' preference for drug eluting or bare metal stents. Issue 3 (7th February 2017) - Qintar, Mohammed; Chhatriwalla, Adnan K.; Arnold, Suzanne V.; Tang, Fengming; Buchanan, Donna M.; Shafiq, Ali; Pokharel, Yashashwi; deBronkart, Dave; Ashraf, Javed M.; Spertus, John A.
Abstract : Objectives: To assess patients' perspective about factors associated with stent choice. Background: Drug eluting stents (DES) markedly reduce the risk of repeat percutaneous coronary intervention (PCI), but necessitate a longer duration of dual anti‐platelet therapy (DAPT) as compared with bare metal stents (BMS). Thus, understanding patients' perspective about factors associated with stent choice is paramount. Methods: Patients undergoing angiography rated, on a 10‐point scale, the importance (1 = not important, 10 = most important) of avoiding repeat revascularization and avoiding the following potential DAPT drawbacks: bleeding/bruising, more pills/day, medication costs and delaying elective surgery. The factor, or group of factors, that was rated highest by each patient was identified. Results: Among 311 patients, repeat revascularization was the single most important consideration to 14.4% of patients, while 20.6% considered avoiding one of the DAPT drawbacks as most important. Most patients (65%) considered avoiding at least one DAPT drawback as important as avoiding repeat revascularization. In no subgroup of patients did more than a quarter of patients prefer avoiding repeat revascularization above all other concerns. Among patients undergoing PCI, more than three quarters received a DES, regardless of their stated preferences (DES use among those most valuing DES benefits, avoiding DAPT drawbacks, or both equally were 78.7%, 86.2%, and 85.6%, respectively, P = 0.56). Conclusion: Most patients reported that avoiding DAPT drawbacks was as important as avoiding repeat revascularization. Eliciting patient preferences regarding stent type can enhance shared decision‐making and allow physicians to better tailor stent choice to patients' goals and values. Trial Registration: Developing and Testing a Personalized Evidence‐based Shared Decision‐making Tool for Stent Selection (DECIDE‐PCI).ClinicalTrials.gov Identifier: NCT02046902. URL:https://clinicaltrials.gov/ct2/show/NCT02046902 © 2017 Wiley Periodicals, Inc.